2020
DOI: 10.1177/0891243220946335
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers, Gender, and the Law: An Analysis of Family Responsibility Discrimination Case Outcomes

Abstract: As workers struggle to combine work and family responsibilities, discrimination against workers based on their status as caregivers is on the rise. Although both women and men feel the pinch, caregiver discrimination is particularly damaging for women, because care is intricately tied to gendered norms and expectations. In this article, we analyze caregiver discrimination cases resolved by Canadian Human Rights Tribunals from 1985 through 2016, to explore how work and caregiving clash. We identify issues invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Protection could also come via Human Rights Codes that prohibit discrimination on the basis of family status, requiring employers to reasonably accommodate family obligations that seriously interfere with work. “Reasonable accommodation” and “serious interference,” however, leave room for interpretation (Hirsh, Treleaven, and Fuller 2020).…”
Section: Background: Employment Care and Schooling In The Pandemicmentioning
confidence: 99%
“…Protection could also come via Human Rights Codes that prohibit discrimination on the basis of family status, requiring employers to reasonably accommodate family obligations that seriously interfere with work. “Reasonable accommodation” and “serious interference,” however, leave room for interpretation (Hirsh, Treleaven, and Fuller 2020).…”
Section: Background: Employment Care and Schooling In The Pandemicmentioning
confidence: 99%
“…Presence in the upper tiers of income for women often means having to succeed in traditionally male-typed professional or managerial jobs [30]. Breaking these cultural barriers while also dealing with a still uneven distribution of housework [31] and gendered expectations about family responsibilities [32] may increase exposure to stressors and therefore be the cause of poorer health among women who spent more years in top family income quartile. It is worth pointing out, however, that these associations were almost statistically significant for men as well, which could point to employment related stressors pertaining to high earning jobs in general.…”
Section: Discussionmentioning
confidence: 99%
“…99 In Canada, an analysis of caregiving discrimination claims brought before the Canadian Human Rights Tribunals from 1985 to 2016 found that cases contesting terminations accounted for 56 percent of the claims brought by women, and 49 percent of caregiving-related claims overall. 100 Discrimination against Workers Caring for Aging Adults and Family Members with Disabilities. Like workers with young children, workers who are balancing paid work with caregiving responsibilities for an aging adult or a family member with a disability often face discrimination at work, particularly if they need to take leave to meet caregiving needs.…”
Section: Discrimination Against Young Women Based On Presumptions Of ...mentioning
confidence: 99%